2010
DOI: 10.1016/j.enbuild.2010.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Study on Auto-DR and pre-cooling of commercial buildings with thermal mass in California

Abstract: This paper discusses how to optimize pre-cooling strategies for buildings in a hot California climate zone with the Demand Response Quick Assessment Tool (DRQAT), a building energy simulation tool. This paper outlines the procedure used to develop and calibrate DRQAT simulation models, and applies this procedure to eleven field test buildings. The results of a comparison between the measured demand savings during the peak period and the savings predicted by the simulation model indicate that the predicted dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(66 citation statements)
references
References 17 publications
0
63
0
Order By: Relevance
“…Market platforms, a regulatory environment that rewards smart consumer behavior, and automation infrastructure are successfully presented in field trials [14], but still need improvement and a broader application in other countries. Several demonstration projects that are currently starting show that there is an active research community in this field, and that industry is already implementing their results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Market platforms, a regulatory environment that rewards smart consumer behavior, and automation infrastructure are successfully presented in field trials [14], but still need improvement and a broader application in other countries. Several demonstration projects that are currently starting show that there is an active research community in this field, and that industry is already implementing their results.…”
Section: Discussionmentioning
confidence: 99%
“…One modern system for automated demand response, OpenADR [13], [14], is developed by the leading research group on DR, the Demand Response Research Center (DRRC) at the Lawrence Berkeley National Laboratory. OpenADR is an open specification and an open-source reference implementation of a distributed, client-server oriented DR infrastructure with a publisher-subscriber model.…”
Section: Demand Responsementioning
confidence: 99%
“…Initial research has identified resetting zone temperatures as a promising technique to modify cooling loads on hot summer days . Previous research has included evaluating different HVAC systems as well as examining the use of thermal mass to pre-cool buildings (Yin et al 2010). DR strategies for lighting systems vary based on the type of controls (Rubinstein and Kiliccote 2007).…”
Section: Background and Previous Researchmentioning
confidence: 99%
“…Reference [34] shows the potential for reducing peak electrical demand in moderate-sized commercial buildings by modifying heating, ventilation and air conditioning (HVAC) system control. Peak-load reduction strategy modeling studies by Yin et al [35] developed and calibrated simulation models of 11 commercial buildings for evaluating the effect of different thermostat control strategies.…”
Section: Demand Response Quick Assessment Toolmentioning
confidence: 99%
“…The Demand Response Quick Assessment Tool (DRQAT) is another tool for this application, and is used to develop models for simulating various DR strategies to estimate the demand shedding and shifting potential [35]. DRQAT is based on the modeling engine and capabilities of EnergyPlus [36].…”
Section: Demand Response Quick Assessment Toolmentioning
confidence: 99%